Phonon-assisted heat transfer between vacuum-separated surfaces - Pendry,JB; Sasihithlu,K; Craster,RV (Physical Review B - Condensed Matter and Materials Physics, 2016)
With increasing interest in nanotechnology, the question arises of how heat is exchanged between materials separated by only a few nanometers of vacuum. Here, we present calculations of the contribution of phonons to heat transfer mediated by van der Waals forces and compare the results to other mechanisms such as coupling through near field fluctuations. Our results show a more dramatic decay with separation than previous work.